2009
DOI: 10.1007/s00384-009-0828-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between adiponectin, resistin, insulin resistance, and colorectal tumors

Abstract: Insulin and homeostasis model assessment insulin resistance index (HOMA-IR) levels were higher, and adiponectin levels were significantly decreased in patients versus controls, whereas, resistin levels were significantly increased. A negative correlation between adiponectin, HOMA-IR, and insulin and a positive correlation between HOMA-IR, insulin, and stage were detected. There was no correlation between the stage and resistin. Adiponectin level negatively correlated with the stage. Adiponectin and resistin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 43 publications
6
69
2
4
Order By: Relevance
“…Reduced circulatory levels of adiponectin have been shown in obese patients and implicated in the development of obesity-related malignancy (Yang et al, 2002;Cnop et al, 2003). Low ApN levels were found in breast, endometrial, prostate, colon and gastric cancers (Mantzoros et al, 2004;Ishikawa et al, 2005;Michalakis et al, 2007;Kumor et al;2009;Gonullu et al, 2010;Chen et al, 2012;Gulcelik et al, 2012;Ho et al, 2012). A positive correlation was shown between body-mass index and colorectal cancer in several studies (Murphy et al, 2000;Moore et al, 2004).…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Reduced circulatory levels of adiponectin have been shown in obese patients and implicated in the development of obesity-related malignancy (Yang et al, 2002;Cnop et al, 2003). Low ApN levels were found in breast, endometrial, prostate, colon and gastric cancers (Mantzoros et al, 2004;Ishikawa et al, 2005;Michalakis et al, 2007;Kumor et al;2009;Gonullu et al, 2010;Chen et al, 2012;Gulcelik et al, 2012;Ho et al, 2012). A positive correlation was shown between body-mass index and colorectal cancer in several studies (Murphy et al, 2000;Moore et al, 2004).…”
Section: Association Of Adiponectin Receptor (Adipo-r1/-r2) Expressiomentioning
confidence: 99%
“…Aside from treatment possibilities, adiponectin is a good biomarker for colorectal adenoma patients due to its significant inverse correlation with the number of adenomas [73]. Additionally, low adiponectin levels are associated with insulin resistance as well as stage of colorectal cancer, indicating that low adiponectin is connected to poor prognosis and possibly carcinogenesis [74]. Furthermore, in both human and mouse colon cancer cell lines adiponectin and Metformin combined reversed the effect of IL-1β, an inducer of cancer carcinogenesis via tumor suppressor protein p53 [75].…”
Section: Adiponectinmentioning
confidence: 99%
“…Recent studies have shown an association between low plasma levels and/or tissue expression of adiponectin, along with an increased risk of various malignancies for which there is an established association with increased body weight and/or insulin resistance including breast (Miyoshi et al 2003;Mantzoros et al 2004), endometrial (Petridou et al 2003;Cust et al 2007), colorectal (Wei et al 2005;Yoneda et al 2008;Barresi et al 2009;Byeon et al 2010;Gonullu et al 2010), renal (Spyridopoulos et al 2007), and prostate (Mistry et al 2006) cancers, as well as leukemia (Molica et al 2009). …”
mentioning
confidence: 99%